Haicai e poesia visual: tessituras/tecituras da poesia brasileira à luz da semiótica - Lira, Janaína da Conceição Jerônimo (2021)
This research aimed at comparing the visual poetry and haiku, having as investigative impulse the aesthetic contributions of these poetic forms to contemporary poetry in our country. In order to achieve our goal, we chose Augusto de Campos´ visual poems and the Haiku by Paulo Leminski. Then, it was verified which poetics aspects of these authors narrow and / or distance aesthetically, and what the theoretical consequences of such narrowing or distancing are. To compose the corpus of this research it was chosen the poems by Augusto, present in his work: Viva Vaia (2014), which contains poems from 1959 to 1979. It was also used Leminski Haiku´s, which presents visual aids in their constitution, Caprichos & relaxos (2016). The corpus analysis of the research was carried out having as a background the General Theory of Signs, elaborated by the American thinker Charles Sanders Peirce. Thus, it was prioritized the three categories of the sign that form the most important of the trichotomies considered by the North American researcher in his speculative grammar: the symbol, the index and the icon; of this last category, it was emphasized its subclassification: the image, the diagram and the metaphor. It was used as theoretical contributions the studies of Haroldo de Campos (2000), Ernest Fenollosa (2000), Ferraz Jr. (2012), Roman Jakobson (1995), Winfried Nöth (2003), Charles S. Peirce (2015), Décio Pignatari (2004), Ezra Pound (2006) e Lúcia Santaella (2012), among other authors. We found out that one of the biases that narrows the poetics of these authors is an inclination towards dialogue with the Eastern tradition, based on the way of composing inspired by Japanese ideograms whose influence was a “watershed” for many Western poets in the 20th century, reverberating also in the productions of the 21st century.